Assessment of Teachers' Professional Misconduct in Secondary Schools in ldcmili South Local Government Area, Anambra State, Nigeria. - OGBUDINKPA, Ijeoma Charit; OLUWALOLA, Felicia Kikelomo (International Journal of Educational Management, 2025)
T he study assessed the effects of teachers'professional misconduct in secondary schools in Idemili South Local Government Area, Anambra State. The objectives of the study were to: (i)examine the professional misconduct mostly practiced by secondary school teachers in Jdemili south local government area, Anambra state;(ii) examine the causes of these professional misconducts;(iii) determine the relationship between teachers' professional misconduct, and secondary school effectiveness in Jdemili south local government area, Anambra state;(iv) investigate the level ofteachers'professional misconduct in Idemili south local government area, Anambra State. T he study adopted a descriptive research design of correlational type. Four research questions were raised to guide the study. The study covered 75 secondary schools in Jdemili South Local Government Area, Anambra State (both private and public). Out of these schools, 20 secondary schools were selected for the study based on the year of establishment. This therefore gave a total number of 20 participants since only the principals are needed for the study. Mean and Standard Deviation were used to analyze the data obtained from the respondents. The three null hypotheses were tested at 0. 05 levels using Pearson's Product Moment Correlation (PPMC). T he findings showed seduction and sexual abuse of students, teachers' regular absenteeism, teachers' unethical dressing, involvement in examination malpractices, e xtortion and corruption among the teachers, are the professional misconducts mostly practiced by the secondary school teachers in Idem iii South LGA, AnambraState. Based on the findings and conclusion of this study, it was recommended among others that the school should set up a disciplinary committee and any teacher caught with any of the misconduct should be punished accordingly.